Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00784-018-2458-2
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding related to dental treatment in patients taking novel oral anticoagulants (NOACs): a retrospective study

Abstract: Our study suggests that patients taking NOACs who need dental treatments may have a bleeding tendency based on our retrospective data. Preoperative history taking and treatment modification should therefore be considered before performing dental surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 16 publications
0
29
0
2
Order By: Relevance
“…Although 21 studies were included in the review, only six studies (Johnston, ; Kwak et al., ; Lababidi et al., ; Miller & Miller, ; Patel et al., ; Zeevi et al., ) and two case‐series studies (Breik et al., and Hassona et al., ) reported on a direct comparison between these two groups of patients. The remaining 13 articles analyzed bleeding events in patients who had all discontinued DOAC therapy before surgery (Abayon et al., ; Gómez‐Moreno et al., ; Miclotte et al., ) or who continued it unchanged (Andrade et al., ; Berton et al., ; Caliskan et al., ; Clemm et al., ; Gómez‐Moreno et al., ; Hanken et al., ; Mauprivez et al., ; Miranda et al., ; Morimoto et al., ; Yagyuu et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although 21 studies were included in the review, only six studies (Johnston, ; Kwak et al., ; Lababidi et al., ; Miller & Miller, ; Patel et al., ; Zeevi et al., ) and two case‐series studies (Breik et al., and Hassona et al., ) reported on a direct comparison between these two groups of patients. The remaining 13 articles analyzed bleeding events in patients who had all discontinued DOAC therapy before surgery (Abayon et al., ; Gómez‐Moreno et al., ; Miclotte et al., ) or who continued it unchanged (Andrade et al., ; Berton et al., ; Caliskan et al., ; Clemm et al., ; Gómez‐Moreno et al., ; Hanken et al., ; Mauprivez et al., ; Miranda et al., ; Morimoto et al., ; Yagyuu et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the six studies, one study was assessed as good quality, four were evaluated as fair quality, and one of poor quality (Table ). Risk of bias of the 21 studies was assessed using the Newcastle‐Ottawa scale: two studies received a low risk of bias score (seven stars, Miller & Miller, ; Zeevi et al., ), 16 studies received a high risk of bias score (six stars, Andrade et al., ; Berton et al., ; Caliskan et al., ; Clemm et al., ; Gómez‐Moreno et al., , ; Hanken et al., ; Kwak et al., ; Lababidi et al., ; Mauprivez et al., ; Miclotte et al., ; Miranda et al., ; Morimoto et al., ; Patel et al., ; Yagyuu et al., and five stars, Johnston, ), and three case‐series received a very high risk of bias score (one star, Abayon et al., ; Breik et al., ; Hassona et al., ; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears there is no need for interruption of NOAC therapy in most dental treatments, due to a low incidence of bleeding complications, which can be successfully managed with local haemostatic measures when comparing groups continuing NOAC and groups discontinuing NOAC therapy (Kwak et al, ; Lababidi et al, ; Patel et al, ; Yagyuu et al, ) and with reported timing of discontinuation and reinstitution varying greatly. When comparing NOAC patients with healthy individuals, there seems to be a higher incidence of delayed bleeding (2 days and later) in those patients who do not discontinue NOAC therapy (Miclotte et al, ).…”
Section: Cardiovascular Risks and Complications Of Periodontal Therapmentioning
confidence: 99%
“…It appears there is no need for interruption of NOAC therapy in most dental treatments due to a low incidence of bleeding complications, which can be successfully managed with local haemostatic measures when comparing groups continuing NOAC and groups discontinuing NOAC therapy [58,59,92,137], and with reported timing of discontinuation and reinstitution varying greatly. When comparing NOAC patients with healthy individuals, there seems to be a higher incidence of delayed bleeding (2 days and later) in those patients who do not discontinue NOAC therapy [78].…”
Section: Novel/direct Anticoagulants (Doac/noac)mentioning
confidence: 99%